2018
DOI: 10.1590/1807-3107bor-2018.vol32.0080
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bulk-fill systems: microtensile bond strength and non-destructive imaging of marginal adaptation

Abstract: The objective of this study was to investigate microtensile bond strength (MTBS) and interfacial adaptation (IA) of bulk-fill restorative systems bonded to dentin in Class-I-preparations. Box-shaped preparations (4-mm-long, 3-mm-wide, 2-mm-high) made in extracted molars, and Teflon matrix with the same dimensions positioned over the occlusal surface were restored, providing a total of 4-mm composite depth using three bulk-fill restorative systems: Tetric EvoCeram Bulk Fill with Tetric N-Bond (TEC/TNB), SureFil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
1
7
0
2
Order By: Relevance
“…35 In contrast, our findings showed that Bulk Fill did not present better microleakage; instead, it was similar to that of conventional resin. These findings corroborate those by Fronza et al, 34 who found no microleakage differences between conventional and bulk-fill resin. In addition, Scotti et al 35 also demonstrated that conventional composite resin and bulk-fill resin showed similar microleakage values at the enamel margins.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…35 In contrast, our findings showed that Bulk Fill did not present better microleakage; instead, it was similar to that of conventional resin. These findings corroborate those by Fronza et al, 34 who found no microleakage differences between conventional and bulk-fill resin. In addition, Scotti et al 35 also demonstrated that conventional composite resin and bulk-fill resin showed similar microleakage values at the enamel margins.…”
Section: Discussionsupporting
confidence: 92%
“…Bulk-fill resins present a lower modulus of elasticity and lower wettability than conventional resins; therefore, better microleakage is expected. 34 Microleakage is an important parameter of marginal adaptation, and directly influences the longevity of restorations; it can lead to the repair or replacement of the restoration, depending on how the restoration fails. 35 In contrast, our findings showed that Bulk Fill did not present better microleakage; instead, it was similar to that of conventional resin.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous resin composite materials were studied over the past years, including conventional and bulk-fill composites [16][17][18][19][20][21][22]. With regards to laboratory outcomes, the bulk-fill materials show better or similar performance than the conventional materials in terms of volumetric shrinkage, polymerization stress, cusps deflection and marginal quality [23].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the effect of storage time on µTBS regardless of RC material, the µTBS bond strength values adversely affected by time. This could be explained by the biodegradation process of resin-based materials over time, where the daily rate of consumption of aqueous solutions drastically affects the µTBS of the resin-based materials [40], [41], [42].…”
Section: Discussionmentioning
confidence: 99%